2020
DOI: 10.1093/cdn/nzaa170
|View full text |Cite
|
Sign up to set email alerts
|

Intermittent Bolus Feeding Enhances Organ Growth More Than Continuous Feeding in a Neonatal Piglet Model

Abstract: Background Orogastric tube feeding is frequently prescribed for neonates who cannot ingest food normally. In a piglet model of the neonate, greater skeletal muscle growth is sustained by upregulation of translation initiation signaling when nutrition is delivered by intermittent bolus meals, rather than continuously. Objective The objective of this study was to determine the long-term effects of feeding frequency on organ gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…Circulating insulin and amino acid concentrations during the last day of feeding were reported previously (4,23) but are reported here for context. Plasma insulin and amino acid concentrations were constant in the CTS group [insulin = 5.6 ± 0.4 μU/mL; branched-chain amino acid (BCAA) = 1333 ± 94 μmol/L].…”
Section: Hormones and Substratesmentioning
confidence: 62%
See 3 more Smart Citations
“…Circulating insulin and amino acid concentrations during the last day of feeding were reported previously (4,23) but are reported here for context. Plasma insulin and amino acid concentrations were constant in the CTS group [insulin = 5.6 ± 0.4 μU/mL; branched-chain amino acid (BCAA) = 1333 ± 94 μmol/L].…”
Section: Hormones and Substratesmentioning
confidence: 62%
“…Previously, we reported that intermittent bolus feeding induces higher rates of protein synthesis in skeletal muscle than continuous feeding in a neonatal piglet model (4,23), resulting in an increase in lean growth (4). These results are supported by the findings that intermittent bolus feeding elicits cyclical hormone and substrate patterns in neonatal pigs (24) and preterm human infants (27), and suggest that the insulin and amino acid surges induce greater anabolic activation of the signaling networks that regulate protein synthesis (4,23). However, the molecular mechanisms by which intermittent feeding promotes greater lean growth than continuous feeding have not been fully delineated.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although continuous feeding may improve feeding tolerance and glycemic stability, the absence of recurring surges in insulin and amino acids may limit muscle protein synthesis and consequently lean growth in the neonate (19)(20)(21)(22). Indeed, prolonged intermittent bolus feeding promotes body weight gain and increases lean mass compared with continuous feeding in neonatal pigs born at term (23,24).…”
Section: Introductionmentioning
confidence: 99%